Gender Disparities in India’s Sterilisation Policy and Practice: Ethical Concerns and Human Rights Violations (International Journal of Food and Nutritional Sciences, 2022)
In the post-independence era, India’s rapidly growing population became a major concern due to its potential to hinder economic development, strain resources, and exacerbate poverty. Government’s view sterilisation as a long-term, cost-effective form of contraception, helping to reduce birth rates and improve family planning outcomes. In India rising population also posed challenges for healthcare, education, housing, and employment, affecting overall social and economic progress also aimed at improving maternal and child health by preventing unintended pregnancies.